1999
DOI: 10.1128/iai.67.12.6631-6636.1999
|View full text |Cite
|
Sign up to set email alerts
|

Calgranulin C Has Filariacidal and Filariastatic Activity

Abstract: The calgranulins are a family of calcium- and zinc-binding proteins produced by neutrophils, monocytes, and other cells. Calgranulins are released during inflammatory responses and have antimicrobial activity. Recently, one of the calgranulins, human calgranulin C (CaGC), has been implicated as an important component of the host responses that limit the parasite burden during filarial nematode infections. The goal of this work was to test the hypothesis that human CaGC has biologic activity against filarial pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 42 publications
(55 reference statements)
0
40
0
Order By: Relevance
“…The antibacterial properties of the amino terminal 60 residues of prophenin-1, primarily directed against gram negative organisms, have long been known [18,23], and recently it has been shown that, even in the presence of a lung surfactant preparation, an 18-residue carboxy terminal fragment also possesses antibacterial activity [9,35]. Calgranulin C belongs to a family of calcium-and zinc-binding proteins and also possesses antimicrobial as well as filariacidal activity [16]. Because PR-39 has been reported to be increased in serum after infection [39] and, because this antimicrobial peptide is involved in wound repair processes [12], we hypothesised that PR-39 might be an appropriate disease marker in BALF facilitating the detection of convalescent animals, which still might be carriers of the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial properties of the amino terminal 60 residues of prophenin-1, primarily directed against gram negative organisms, have long been known [18,23], and recently it has been shown that, even in the presence of a lung surfactant preparation, an 18-residue carboxy terminal fragment also possesses antibacterial activity [9,35]. Calgranulin C belongs to a family of calcium-and zinc-binding proteins and also possesses antimicrobial as well as filariacidal activity [16]. Because PR-39 has been reported to be increased in serum after infection [39] and, because this antimicrobial peptide is involved in wound repair processes [12], we hypothesised that PR-39 might be an appropriate disease marker in BALF facilitating the detection of convalescent animals, which still might be carriers of the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Another secreted protein, CS-VI, also termed as neutrophil antibiotic peptide NP-6 [30], was found in the egg samples. Calgranulin C, another antimicrobial protein, was reported to be secreted by activated neutrophils onto the worm surface of Onchocerca volvulus for eliciting the antifilarial effect [31,32]. The antimicrobial protein CAP18, an essential component of the mammalian innate immune system [33,34], were also found in the egg samples.…”
Section: Host Innate Immune System Could Play Important Roles Againstmentioning
confidence: 99%
“…Host DJ-1, a molecule playing a role in antioxidative stress by eliminating reactive oxygen species [46], is also helpful for schistosome eggs when evading host's attacks. The most abundant host protein found in the adult worm sample of S. japonicum is a proteinase inhibitor, Serpin A 3K (30 MS/MS, combined MASCOT score, 2169, Table 2 and Supplementary Table 3), by which the schistosome may counteract or attenuate toxic enzymes such as elastase released by host neutrophils [31,32]. Another host proteinase inhibitor, Serpin A 3M, was also found in adult worm sample.…”
Section: Antagonistic Strategy Of Schistosome For Evading Host Attacksmentioning
confidence: 99%
“…This suggests that EN-RAGE may not suppress the survival of M. leprae, unlike the report indicating that EN-RAGE has a filaricidal effect on Brugia malayi in vitro. 30 EN-RAGE may be induced by M. leprae per se or its wall components; subsequently, TNF-a is released by inflammatory cells infiltrated in MB leprosy lesions, which, in turn, may induce EN-RAGE expression.…”
Section: En-rage-positive Cells (Mean ± Sd)mentioning
confidence: 99%